Kepuasan Peternak Ayam Broiler Pada Sistem Kemitraan di Kecamatan Padang Jaya Kabupaten Bengkulu Utara: Satisfaction of Broiler Chicken Farmers in The Partnership System in Padang Jaya District,North Bengkulu Regency - Lestari, Indah Tri; Santoso, Urip; Yurike, Yurike (Buletin Peternakan Tropis, 2025)
This study aims to analyze the level of satisfaction of broiler chicken farmers with the partnership system in Padang Jaya District, North Bengkulu Regency. The partnership system is one of the livestock business patterns that is growing rapidly in this area, where the partner company provides livestock production facilities (sapronak), technical assistance, and collects the harvest, while the farmers as plasma are responsible for maintenance. The research method used a quantitative descriptive approach with a survey technique on a number of plasma farmer respondents who are members of the partnership. Data were collected through questionnaires, interviews, and observations, then presented in tabular form and analyzed descriptively. The results showed that farmer satisfaction with the broiler chicken partnership system had the highest average value in the first place, namely in the economic capital variable (94%) because the farmers do not require too much capital, the company provides capital such as feed, seeds (DOC), as well as medicines and vaccines. Meanwhile, the lowest average value was found in distribution (77%) because the farmers are already bound by contracts with the company so they do not have freedom, selling prices are set unilaterally, irregular harvest scheduling, a less efficient harvesting system, and lack of involvement in every decision. These findings indicate that improving the quality of partnership services and transparency of collaboration can increase satisfaction and the sustainability of broiler chicken partnership patterns in Padang Jaya District.